Արդի հայերենի նորմը և հեռուստատեսության լեզուն - Թելյան, Լ. Գ.
В статье приводится ряд отклонений от языковой нормы и ошибок, зафиксированных автором в результате наблюдений языка телевидения. Эти отклонения классифицируются и оцениваются с позиций языковой нормы современного армянского языка. The article presents a number of deviations from the linguistic norm and errors, recorded by the author as a result of observing the language of television. These deviations are classified and evaluated from the standpoint of the linguistic norms of the modern Armenian language.
Keywords: Լեզվաբանություն